Clinical presentation and outcome by age categories in acute heart failure: results from an international observational cohort. (30th September 2015) - Teixeira, Antonio; Parenica, Jiri; Park, Jin Joo; Ishihara, Shiro; AlHabib, Khalid F.; Laribi, Said; Maggioni, Aldo; Miró, Òscar; Sato, Naoki; Kajimoto, Katsuya; Cohen‐Solal, Alain; Fairman, Enrique; et al.
Abstract : Aims: To assess, according to age groups, patients' characteristics according to region of origin, the chronic therapeutic management, prognostic utility of clinical variables, and natriuretic peptides. Methods and results: The GREAT registry consisted of patients identified as presenting with acute heart failure at the emergency department. Four groups of patients were defined according to age: the young patient group (<65 years); 'middle‐old' (65–74 years), 'old‐old' (75–84 years) and the 'oldest‐old' (85–94 years). Follow‐up at 1 year was performed via personal contact or national data registries at 1 year. Dataset consisted of 14 758 patients aged up to 95 years, with the 'oldest‐old' group being more prevalent in North America and Western Europe. The 30‐day mortality rate were, respectively, 8.1%, 8.9%, 10.3%, and 16.3% among the four age groups and 1‐year mortality rates were, respectively, 3.1%, 17.1%, 24.7%, and 39.9%. Chronic heart failure treatment was less frequently administered with age (percentage of the 'fully treated' group was 14% in the 'young' compared with 2% in the 'oldest‐old' patient group). Reduced left ventricular ejection fraction was present in 70%, 62.3%, 52.5%, and 46.8% among the four age groups, respectively. The prognostic utility of most variables for short‐ and long‐term outcome was attenuated with age, with the exception of natriuretic peptides. Conclusion: This study found a large heterogeneity in age among geographic regions and that the eldest are less likely to be treated in accordance with recommendations of current heart failure guidelines. Natriuretic peptide concentrations retained prognostic value in patients across age strata.